3(2y+3)-4=-3

Simple and best practice solution for 3(2y+3)-4=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2y+3)-4=-3 equation:


3(2y+3)-4=-3

We simplify the equation to the form, which is simple to understand
3(2y+3)-4=-3

Reorder the terms in parentheses
+(+6y+9)-4=-3

Remove unnecessary parentheses
+6y+9-4=-3

We move all terms containing y to the left and all other terms to the right.
+6y=-3-9+4

We simplify left and right side of the equation.
+6y=-8

We divide both sides of the equation by 6 to get y.
y=-1.33333333333

See similar equations:

| -x^4-14x^2+15=0 | | 5-2x=13-7x | | x^4-14x^2+15=0 | | -5x+3y=6 | | 13y^2-117y+104=0 | | 9x-42=4x-7 | | 1.8x+29=4x-4 | | 30x^2-18x-12=0 | | 0.625b-6=0.5b+12 | | 6y^2-22y-40= | | (7X+18)=67 | | 3x-4x=-13 | | 4x^2-8x+7=0 | | x+0.1x=-25.4 | | 0.75w-5=1-0.75w | | 3x^3+9=0 | | (4x^2-2x)+1= | | 5y-5=-26-2y | | x^3-12x^2+32x= | | -3x^2+75= | | j=38n-4 | | (3x^2+4x-1)(x)+(3x^2+4x-1)(4)= | | -10x+7=-23 | | 20x^3=5x | | 3(2*+1)-4*=1*+19 | | -3x(x-8)= | | 10c^2+29c+10= | | (2x-7)(7x+2)= | | 10-29c+10c^2= | | x^2+12=6x+3 | | 3(-2x+1)--4x=-1+19 | | (2x+3)(4x-5)= |

Equations solver categories